2010
DOI: 10.1108/16605371011083530
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficacy of organizational support and personality traits in predicting service recovery and job performances: a study of frontline employees in Turkey

Abstract: Purpose -The purpose of this paper is to examine the relative efficacies of a set of organizational support mechanisms and personality traits in predicting frontline employees' service recovery and job performances.Design/methodology/approach -Data were gathered through self-administered questionnaires. A sample of 723 frontline hotel employees in Turkey serves as the study setting. Findings -The study results show that organizational support is more effective in differentiating between high-and low-performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 80 publications
(90 reference statements)
7
59
0
Order By: Relevance
“…Yavas et al (2003) reported that empowerment positively influenced frontline bank employees' service recovery performance in Turkey. Recently, Yavas et al (2010) also indicated that training and empowerment triggered frontline employees' service recovery performance in Turkish hotels. Accordingly, the following hypotheses are proposed:…”
Section: Management Commitment To Service Quality and Performance Outmentioning
confidence: 99%
See 2 more Smart Citations
“…Yavas et al (2003) reported that empowerment positively influenced frontline bank employees' service recovery performance in Turkey. Recently, Yavas et al (2010) also indicated that training and empowerment triggered frontline employees' service recovery performance in Turkish hotels. Accordingly, the following hypotheses are proposed:…”
Section: Management Commitment To Service Quality and Performance Outmentioning
confidence: 99%
“…Boshoff, Allen 2000;Yavas et al 2010). Empowered employees would be able to provide quick, appropriate, and equitable responses to complainants (Boshoff, Allen 2000;Yavas et al 2003).…”
Section: Management Commitment To Service Quality and Performance Outmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees having intense face-to-face or voice-to-voice interactions with customers play the most critical role in this process (Cheng et al, 2008;Weber and placeCitySparks, 2010;Yavas et al, 2010). Such employees are also among the main actors who can return disgruntled customers to a state of satisfaction after a service failure (Yavas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Employees having intense face-to-face or voice-to-voice interactions with customers play the most critical role in this process (Cheng et al, 2008;Weber and placeCitySparks, 2010;Yavas et al, 2010). Such employees are also among the main actors who can return disgruntled customers to a state of satisfaction after a service failure (Yavas et al, 2010). In addition, according to the resource-based view, inimitable human resources (e.g., highly quali…ed frontline employees) are pivotal in service delivery process (Jerman and Završnik, 2006;Karatepe and Aleshinloye, 2009).…”
Section: Introductionmentioning
confidence: 99%